Microbiological and parasitological monitoring in the lettuce production chain of family farming - de Arruda, Maria Cecília; Marques Jeronimo, Elisangela; Rossi, Renan; Fischer, Ivan Herman; Boarato David, Erica; Antunes, Andrea Maria (Comunicata Scientiae, 2021)
Lettuce is a vegetable consumed raw and can be a vehicle for diseases caused by microrganisms and parasites. The objective of this work was to carry out microbiological and parasitological monitoring in the production chain of lettuce, determining the main points of contamination during cultivation, harvest and handling. Microbiological analyses were performed on samples of organic compost, irrigation water, waste water from the wash tank, water that supplies the wash tank, lettuce, lanyard hands, surfaces of the wash tank and harvest box, during six production cycles. Parasite analyzes were performed on organic compost, water samples and lettuce. The irrigation water proved to be of excellent quality. The organic compost used for fertilization did not meet the microbiological limits established by current legislation and all samples presented Entamoeba spp cysts. E.coli was detected in the hand of the harvester (3rd cycle), in the harvest box (5th cycle) and in the samples of residual water from the pre-wash and water that supplies the pre-wash tank. The contamination points detected were not directly related to the contamination of the harvested lettuce. Of the lettuce samples analyzed, only 3% showed unacceptable quality according to current legislation.